A Case Report of Orbital Venolymphatic Malformation - A diagnostic dilemma - Sunda, Priyanka; Jakhar, Ankita; Farooq, Shaheen; Shweta; Bothra, Mohnish; Kochar, Anju (Nepalese Journal of Ophthalmology, 2024)
Introduction: Intermittent proptosis is a transitory position-dependent protrusion of one or both eyeballs beyond orbit. The common causes of proptosis in young females are tumors, inflammation, trauma, thyroid eye disease and vascular lesions. The case report highlights the importance of imaging in prone position. Case: We report a rare case of a 24-year-old female who recently developed intermittent proptosis while bending forwards. The patient was evaluated clinically. Ultrasonography B scan, Computerised axial tomography (CT), Magnetic resonance imaging (MRI) were advised to rule out orbital varices, arteriovenous aneurysm, or any organic lesion. Probable diagnosis of venolymphatic malformation was made. Conclusion: An intertwined approach was carried out with Ophthalmologist and Radiologist to arrive at the final diagnosis highlighting the importance of imaging in prone position.